KOMUNIKASI PARIWISATA DALAM PENGEMBANGAN POTENSI WISATA RELIGI DI KALIMANTAN SELATAN: KOMUNIKASI PARIWISATA DALAM PENGEMBANGAN POTENSI WISATA RELIGI DI KALIMANTAN SELATAN - Rawali, Siswanto; Muthahari Ramadhani, Muhammad (Fakultas Ilmu Komunikasi Universitas Teknologi Sumbawa, 2024)
The well-planned development of a religious tourism attraction not only provides economic benefits that improve the standard, quality and lifestyle of local communities but also improves and maintains a good environment. However, it needs to be realized that there is a need for calibration and ideas regarding strategies for developing religious tourism in South Kalimantan. The aim of this research is to increase and improve knowledge regarding development strategies in the government sector that can be used by religious tourism-based tourist attractions as well as practical references to improve development and management of innovative and technology-based religious tourist attractions in South Kalimantan. The research results show that a sustainable tourism strategy implemented by the government really needs full support and participation from the existing community. In the end, it is hoped that a religious tourism climate that is conducive to the growth and development of tourism in South Kalimantan will be created that is competitive in Indonesia and even at the international level. This can be started by using technology and Big Data so that one tourist attraction can be connected to another tourist attraction, both website-based and application-based with collaboration between the Regional Government and related departments, such as the Communication and Information Service and related agencies. Keywords: Tourism Communication, Communication Strategy, Government Innovation, Religious Tourism, South Kalimantan.